A arte de contar hist??rias: um recurso did??tico para a forma????o de leitores. - Santos, Gislene Aparecida da Silva (2009)
This study aims to explore the formation of starting readers using as teaching resource the story telling, activity that is often discredited in the reading classes. Based on Nelly Novaes Coelho and C??mara Cascudo research and conception, this document discusses the reader s formation in view of aesthetic and cultural factors existed in the story telling. This is examined as a didactic contributor for the reader to get charmed with the world of reading and its fantastic stories. So the reader s formation techniques are addressed, so as the story telling techniques used by the traditional and current tellers. The reflection about how to tell stories can captivate the starter reader and permeates all the text, verifying if the techniques of story telling can get the students closer to the books. If the story telling expands the interest for reading, and if a fruitful relationship between reading and hearing stories exist. The proof that the story telling talent stimulates the interest for reading at the same time that it teaches the starter reader to recognize and identify narrative structures will be supported in the reports of teachers/tellers and on bibliographic studies regarding this subject. In the final chapter you can observe the appreciation of the readers and the oral literature in the construction of great names of the literature, confirming the theory that the art of telling stories contributes to the human formation the reader.